Approaches for network based drug discovery - Priyanka Jayachandran; Suganya Ilango; Biswaranjan Paital; Shravani Bhanja; Ramalingam Nirmaladevi (Frontiers in Bioscience-Scholar, 2021)
Molecular network-based studies have gained tremendous importance in biomedical research. Several such advanced technologies in molecular biology have evolved in the past decade and have contributed to building up enormous molecular data. These molecular networks gained much significance among researchers triggering widespread use of experimental and computational tools. This interest led researchers to compile data of biomolecules systematically and to develop various computational tools for analyzing data. In the present scenario, an enormous amount of molecular network databases are available which can be accessed freely by the public. This is the central focus of this article.